2004
DOI: 10.1245/aso.2004.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Genetic Diagnosis With the Transcription?Reverse Transcription Concerted Reaction System for Cancer Micrometastasis

Abstract: Molecular diagnosis of peritoneal lavage fluid with the TRC reaction could be a useful prognostic indicator for peritoneal recurrence and survival. Because the TRC reaction is more rapid and simpler than reverse transcriptase-polymerase chain reaction as a format for detecting RNA sequences, it may enhance the genetic diagnosis of cancer micrometastasis and may improve cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 21 publications
0
48
2
1
Order By: Relevance
“…We applied the method with CEA as a marker for the detection of free cancer cells in peritoneal washes. The sensitivity and quantifi cation of the TRC reaction for the detection of occult cancer cells in peritoneal washes were comparable to those of the conventional quantitative RT-PCR with the LightCycler [37]. It is anticipated that these post-PCR diagnostic systems will contribute to the clinical application of genetic diagnosis in the near future.…”
Section: Novel Molecular Techniques For Detection Of Micrometastasismentioning
confidence: 85%
See 1 more Smart Citation
“…We applied the method with CEA as a marker for the detection of free cancer cells in peritoneal washes. The sensitivity and quantifi cation of the TRC reaction for the detection of occult cancer cells in peritoneal washes were comparable to those of the conventional quantitative RT-PCR with the LightCycler [37]. It is anticipated that these post-PCR diagnostic systems will contribute to the clinical application of genetic diagnosis in the near future.…”
Section: Novel Molecular Techniques For Detection Of Micrometastasismentioning
confidence: 85%
“…The TRC method is superior to the RT-PCR method in rapidity and simplicity (Fig. 3) [37]. We applied the method with CEA as a marker for the detection of free cancer cells in peritoneal washes.…”
Section: Novel Molecular Techniques For Detection Of Micrometastasismentioning
confidence: 99%
“…Current experimental studies which aim to identify a rapid, accurate, and cost-effective detection method are ongoing. The transcription-reverse transcription concerted reaction (TRC) system, as described by Ishii et al [27] and Ohashi et al [51], and the LightCycler system described by Kodera et al [52] have shown promise in IFCC detection by providing results in as little as 1-2 h. Cost, however, still remains a considerable limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, an additional complicating factor in the domain of preoperative staging is the advent of novel, more sensitive methods of detecting micrometastatic disease using immunohistochemical methods or RT-PCR [44], as alluded to earlier in this discussion. Papanicolaou staining remains the current 'gold standard' because of the various limitations in immunohistochemical and molecular methods including (but not limited to) the laborious processes required, the high costs involved, and the possibility of false-positive results with illegitimate transcription of noncancerous cells [45,46]. These factors, and the differences between protocols and procedures between the 'East' and 'West,' prevent any possible adoption of these new techniques addressed by this study to any population.…”
Section: Discussionmentioning
confidence: 99%